Regulation of acetylcholine receptor gene expression in human myasthenia gravis muscles. Evidences for a compensatory mechanism triggered by receptor loss. - T Guyon; A Wakkach; S Poea; V Mouly; I Klingel-Schmitt; P Levasseur; D Beeson; O Asher; S Tzartos; S Berrih-Aknin (The Journal of Clinical Investigation, 1998)
Myasthenia gravis (MG) is a neuromuscular disorder mediated by antibodies directed against the acetylcholine receptor (nAChR) resulting in a functional nAChR loss. To analyze the molecular mechanisms involved at the muscular target site, we studied the expression of nAChR subunits in muscle biopsy specimens from MG patients. By using quantitative PCR with an internal standard for each subunit, we found that the levels of beta-, delta-, and epsilon-subunit mRNA coding for the adult nAChR were increased in severely affected MG patients, matching our previous data on the alpha-subunit. Messenger levels were highly variable in MG patients but not in controls, pointing to individual factors involved in the regulation of nAChR genes. The fetal subunit (gamma-chain) transcripts were almost undetectable in the extrajunctional region of MG muscle, suggesting that gene regulation in MG differs from that in the denervation model, in which nAChR gamma-subunit mRNA is reexpressed. Nicotinic AChR loss mediated by monoclonal anti-nAChR antibodies in both the TE671 muscle cell line and cultured normal human myotubes induces a similar increase in beta- alphand delta-subunit mRNA levels, suggesting the existence of a new muscular signaling pathway system coupled to nAChR internalization and independent of muscle electrical activity. These data demonstrate the existence of a compensatory mechanism regulating the expression of the genes coding for the adult nAChR in patients with MG.